Digital Governance in Logistics Management: Strengthening Good Governance in State-Owned Enterprises - Angga Christopel Immanuel Lumban Tobing; Annada Nasyaya (Faculty of Social and Political Science, 2025)
This study examines the effectiveness of implementing Good Governance principles within a digital-based logistics management system at Warehouse OPT Zone 4A of PT Pertamina Hulu Rokan as part of the broader digital governance transformation in Indonesia’s State-Owned Enterprises (BUMN). Using a descriptive qualitative approach, data were collected through field observation, in-depth interviews with four key informants, and analysis of digital documents from the SAP (System Application and Product) system during June–August 2025. The findings indicate that SAP implementation has significantly improved operational efficiency and accountability, with 94% material receipt accuracy, 82% audit compliance, and only 2.7% delivery delays. The system enhances internal accountability through automated reporting and audit trails while improving coordination across divisions. However, external accountability and public transparency remain limited, as data openness has not yet been institutionalized. Key challenges include limited warehouse capacity, uneven human resource readiness, and dependency on digital infrastructure. Theoretically, this study contributes to the integration of Good Governance and digital governance concepts within State-Owned Enterprises. Practically, it provides strategic recommendations to strengthen data-driven logistics governance, expand open data policies, and enhance digital literacy to achieve greater transparency and accountability in public sector management.